2007
DOI: 10.1128/mcb.00113-07
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Binding Protein HuR Promotes Cell Migration and Cell Invasion by Stabilizing the β-actin mRNA in a U-Rich-Element-Dependent Manner

Abstract: A high expression level of the ␤-actin protein is required for important biological mechanisms, such as maintaining cell shape, growth, and motility. Although the elevated cellular level of the ␤-actin protein is directly linked to the long half-life of its mRNA, the molecular mechanisms responsible for this effect are unknown. Here we show that the RNA-binding protein HuR stabilizes the ␤-actin mRNA by associating with a uridine-rich element within its 3 untranslated region. Using RNA interference to knock do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
120
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(135 citation statements)
references
References 76 publications
(122 reference statements)
14
120
1
Order By: Relevance
“…Transfecting these plasmids into caspase-9 À / À MEFs showed that mutating the AREs caused 480% decrease in the expression of caspase-9 mRNA (Figures 3b and c). Using these cells in an actinomycin D (ActD) pulse-chase experiment, 32 we observed that mutated caspase-9 mRNA had a reduced half-life (of B4.1 h) compared with full-length caspase-9 mRNA (B6.6 h; Figures 3d and e and Supplementary Figure 4). Although AREs are generally known to destabilize their host messages, our data clearly suggest that in the case of caspase-9 mRNA, they are in fact required for its stabilization.…”
Section: Resultsmentioning
confidence: 99%
“…Transfecting these plasmids into caspase-9 À / À MEFs showed that mutating the AREs caused 480% decrease in the expression of caspase-9 mRNA (Figures 3b and c). Using these cells in an actinomycin D (ActD) pulse-chase experiment, 32 we observed that mutated caspase-9 mRNA had a reduced half-life (of B4.1 h) compared with full-length caspase-9 mRNA (B6.6 h; Figures 3d and e and Supplementary Figure 4). Although AREs are generally known to destabilize their host messages, our data clearly suggest that in the case of caspase-9 mRNA, they are in fact required for its stabilization.…”
Section: Resultsmentioning
confidence: 99%
“…Amplimers for ␤ actin were 5Ј-GTGGGCCGCTCTAGGCACCAA-3Ј (forward) and 5Ј-TCTTTGATGTCACGCACGATTTC-3Ј (reverse). COX-2 and ␤-actin mRNAs were assessed as positive controls for HuR immunoprecipitation in vehicle and IL-1␤-treated cells because both are targets of HuR (49,50). PCR products, separated in either a 1% (␤-actin) or 2% agarose (xCT and COX-2) gel containing ethidium bromide (200 g/ml), were visualized with the LI-COR Odyssey Fc infrared imaging system.…”
Section: Methodsmentioning
confidence: 99%
“…3B). Immunoprecipitation of HuR protein also pulled down COX-2 and ␤-actin mRNAs, both of which are known targets of HuR (49,50).…”
Section: Il-1␤ Treatment Enhances Hurmentioning
confidence: 99%
“…Hu/ELAV proteins are known to specifically target localized RNAs in other systems, although no indications for a direct function of Hu/ELAV proteins in RNA localization have been described to date. In particular, HuR was reported to bind to the 3Ј-UTR of ␤-actin mRNA, which localizes to the leading edge of migrating cells, a process that also involves the Vg1RBP homolog ZBP1 (76,77). It was demonstrated that depletion of HuR results in a reduced migratory capacity of such cells, perhaps as a consequence of reduced ␤-actin mRNA stability (76).…”
Section: Data Reported In This Communication Reveal That Xenopusmentioning
confidence: 99%
“…In particular, HuR was reported to bind to the 3Ј-UTR of ␤-actin mRNA, which localizes to the leading edge of migrating cells, a process that also involves the Vg1RBP homolog ZBP1 (76,77). It was demonstrated that depletion of HuR results in a reduced migratory capacity of such cells, perhaps as a consequence of reduced ␤-actin mRNA stability (76). In neurons, the Vg1RBP homolog IMP1, together with HuD, is found to exert a repressing effect on the translation of Tau mRNA 3Ј-UTR reporters (78).…”
Section: Data Reported In This Communication Reveal That Xenopusmentioning
confidence: 99%